Combinatorial technology in heterogenous copper-based catalysis - Ma’amor, Azman (2006)
The combinatorial process allows the exploration of large and diverse compositional and parameter spaces by establishing an integrated workflow of rapid parallel or combinatorial synthesis of large numbers of catalytic materials, subsequent high-throughput assaying of these compounds and large-scale data analysis. The aim of this high-throughput experiment was to develop catalysts with an intrinsically high activity using multiple parallel batch slurry reactors at process condition; pressure at 100 bar H2, temperature at 523K, reaction time of 4 hours and stirring speed at 750 rpm. In this screening phase, over 150 copper based-catalysts have been tested in 2 month. The copper based-catalysts used in the screening were prepared using slurry method at high metal loading. All results from the screening were combined in Access database and analyzed using Spotfire software. The results of catalyst screening were evaluated on the basis of their activity and the trends per family of catalysts. It is found that the catalyst in the family of silica support, Cu-Zn bimetallic and prepared from metal-citrate solution shows better result compared to other catalyst families.